Regional Integration and Economic Growth in the Community of Sahel Saharan States - Michael Ejike Meze; Ezeanyeji C. I (Journal of Social Science and Economics (JOSSE), 2025)
Regional integration is a crucial strategy to foster economic growth, competitiveness, and political stability among developing countries. This study examines the impact of regional integration on economic growth in the Community of Sahel-Saharan States (CEN-SAD) using a composite integration index that encompasses trade, finance, infrastructure, production, and the movement of persons. Grounded in endogenous growth theory, particularly the Lucas model, the research highlights human capital, trade openness, and knowledge spillovers as key drivers of long-term growth. Employing dynamic panel data methods and the System GMM estimator, the study addresses challenges such as endogeneity and heterogeneity among member countries. Key variables include regional integration indices, human and physical capital, institutional quality, and exchange rates. Robustness tests confirm the validity of the model. Results show a positive and significant effect of regional integration on economic growth, primarily through trade, finance, infrastructure development, and the free movement of people. In contrast, production integration shows no significant impact. Economic growth persistence is also observed, with past growth strongly predicting future growth across CEN-SAD countries. These findings suggest that strengthening regional integration and addressing structural challenges will likely enhance economic performance and development in the region. Policy implications include promoting greater collaboration in infrastructure, financial markets, and labor mobility to maximize the benefits of growth.